Microplastics Pollution (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Plastics are amazing products with infinite applications, for example, in food packaging, the aviation and automotive industries, pharmaceuticals, medicine, telecommunication, the apparel industry, etc. Plastic particles less than 5 mm in diameter are considered microplastics, derived from commercial products such as cosmetics, microfibers in textiles, and the degradation of larger plastic waste in the environment. Microplastics have emerged as pervasive pollutants that infiltrate ecosystems, food chains, and even human bodies according to several reports. They have been recognized as a major environmental and human health hazard due to their microscopic size and far-reaching implications this has. Since they take a long time to decompose, microplastics are widespread and they find their way into the food chain via consumption by marine animals. As plastic usage remains high, the release of microplastics into the environment represents an environmental problem of global concern; however, knowledge regarding microplastic accumulation in the environment, their potential impacts, and monitoring approaches is limited. This reprint summarizes the current knowledge on microplastic accumulation, impacts, and monitoring approaches.